Variation for QTL alleles associated with total dissolved solids among crop types in a GWAS of a Beta vulgaris diversity panel - Audrey Pelikan; Irwin L. Goldman (The Plant Genome)
Abstract Sweetness is a main component of the table beet (Beta vulgaris L.) flavor profile and a key determinant of its market success for fresh consumption. Total dissolved solids (TDS) is a proxy for sugar content in produce and are easily measured through a refractometer, making TDS valuable in breeding programs focused on increasing sweetness. A diversity panel of 238 accessions from the Beta vulgaris crop complex and wild relatives was assembled and genotyped using genotyping‐by‐sequencing, yielding 10,237 single nucleotide polymorphisms (SNPs) from 226 full panel accessions and 9,847 SNPs from table beet only accessions after filtering. The panel was phenotyped in field trials over 2 years and mean values were adjusted using best linear unbiased estimates. TDS levels varied among crop types and a broad‐sense heritability of 0.90 indicated that phenotypic differences can be attributed in large part to genetic variation. A genome‐wide association study (GWAS) uncovered four quantitative trait loci (QTLs) identified across multiple models to significantly associate with TDS. A QTL on chromosome 2 was consistently identified among GWAS models, explaining 12.1%–62.6% of the phenotypic variation in the full panel. Bevul.2G176300, a gene directly involved in the sucrose biosynthesis pathway, was located downstream the significant marker. A second QTL identified on chromosome 7 revealed QTL alleles that may differentiate between table beet accessions, explaining nearly half the phenotypic variation, and is the first QTL reported in association with TDS unique to table beet. The QTL described can be used to efficiently breed for higher TDS levels in Beta vulgaris, avoiding intercrop type crosses and linkage drag.